Improving the Fatigue Life of Fusion-Welded Joints Using Shot Peening Method - Che Lah, Nur Azida (2009)
Fusion welding (FW) has been the greatest importance in metal industry application, until today the weld itself still gives significant problems such as porosity and incomplete joint penetration due to the manually handled process. In the present work, FW of ASTM A516 grade 70 carbon steel was characterised in terms of macrostructure, microstructure, hardness, elemental composition, and common internal defects using radiography testing. Fatigue endurance of Manual Metal Arc (MMA), Metal Inert Gas (MIG) and Tungsten Inert Gas (TIG) welded joints were investigated and discussed. Moreover, the assessment of the effectiveness of shot peening in improving fatigue life of FW have been analysed. The results show that the shot peening process greatly improved fatigue strength by removing surface concentration, shifted and closing the discontinuity such as porosity into the internal area. It was seen that the effect of shot peening and skimming process improved the fatigue life of fusion weld (at 190 MPa stress level), it is approximately 78% increase in fatigue life cycles for MMA peened skimmed joint, 94% increase for MIG peened skimmed joint and 90% increase for TIG peened skimmed joint. Based on the observations, the good correlation achieved between the experimental data and previous research suggests that TIG peened skimmed joints shows the greatest quality compared to MMA and MIG regarding to its controllable and cleanest method that can produce high quality weld with low defects. Finally, the findings from this research give the manufacturer better option in joining metals in order to increase their product performance and safety.